A comparison of nontreponemal tests in cerebrospinal fluid for neurosyphilis diagnosis: equivalent detection of specific antibodies - Versiani, Isadora; Cabral-Castro, Mauro Jorge; Puccioni-Sohler, Marzia (Arquivos de Neuro-Psiquiatria, 2019)
Syphilis is a re-emerging sexually-transmitted infection, caused by the spirochete Treponema pallidum, that may penetrate early into the central nervous system. The venereal disease research laboratory test (VDRL) on the cerebrospinal fluid (CSF) is the most widely used for neurosyphilis diagnosis. We evaluated the performance of two other nontreponemal tests (rapid plasma reagin [RPR] and unheated serum reagin [USR] tests) in comparison with the VDRL in CSF.Methods: We analyzed CSF samples from 120 individuals based on VDRL reactivity in the CSF and the clinical picture of neurosyphilis.Results: High inter-rater reliability was found among all three tests, with equivalent sensitivity and specificity. Intraclass correlation coefficient for absolute agreement was 1 for VDRL versus USR, 0.99 for VDRL versus RPR, and 0.99 for RPR versus USR.Conclusions: Rapid plasma reagin and unheated serum reagin tests were identified as excellent alternatives for neurosyphilis diagnosis.
Keywords: cerebrospinal fluid; neurosyphilis